PTPRC (CD45) variation and disease association studied using single nucleotide polymorphism tagging. - Hennig, B; Fry, A; Hirai, K; Tahara, H; Tamori, A; Moller, M; Hopkin, J; Hill, A; Bodmer, W; Beverley, P; Tchilian, E (2008)
CD45 is a haemopoietic tyrosine phosphatase, crucial for lymphocyte signalling. Two polymorphisms (C77G and A138G), which alter CD45 isoform expression, are associated with autoimmune and infectious diseases. Using HapMap data, we show that there is substantial linkage disequilibrium across the CD45 gene (PTPRC), with similar patterns in different populations. Employing a set of single nucleotide polymorphisms, correlated with a substantial proportion of variation across this gene, we tested for association with type 1 diabetes, Graves' disease in a Japanese population, hepatitis C in UK population and tuberculin response in a Chinese population. A limited number of common haplotypes was found. Most 138G alleles are present on only one haplotype, which is associated with Graves' disease, supporting previous data that A138G is a functionally important CD45 polymorphism.